Productivity, water use and economics of potato (Solanum tuberosum L.) + French bean (Phaseolus vulgaris L.) intercropping system as affected by water management - Tyagi, V. K.; Thenua, O.V.S.; Kumar, Dinesh; Singh, Nain (Annals of Agricultural Research, 2014)
A field experiment was conducted on sandy loam soil analysing low in N and medium in P and K during winter season of 2004-05 and 2005-06 at Indian Agricultural Research Institute, New Delhi. The treatments comprised 5 irrigation treatments (irrigation at critical stages of potato, irrigation at critical stages of french bean, and irrigation at 0.8, 1.2 and 1.6 IW/CPE ratio) as main plots and 3 cropping systems (sole potato, sole french bean and potato + french bean in 2:3 row ratio) replicated thrice in a split plot design. The results revealed that irrigation at IW/CPE ratio of 1.6 recorded significantly higher potato equivalent yield (PEY) than all other irrigation treatments, except irrigation at 1.2 IW/CPE ratio in 2004-05. Further, irrigation at critical stages of potato and french bean produced similar PEY. Irrigation at 0.8 IW/CPE ratio recorded the lowest PEY in both the seasons and pooled data. Irrigation at 1.6 IW/CPE ratio had the highest land equivalent ratio (LER) closely followed by irrigation at 1.2 IW/CPE ratio, and the lowest with irrigation at 0.8 IW/CPE ratio. Similar trend was also observed with consumptive water use (CU). Highest water use efficiency (WUE) in sole and intercropped potato was observed with irrigation at the driest regime (irrigation at 0.8 IW/CPE ratio) followed by irrigation at critical stages of potato. In french bean, maximum WUE was observed with irrigation at its critical stages followed by irrigation at critical stages of potato. Based on PEY, the maximum WUE was noticed with irrigation at critical stages of french bean followed by irrigation at critical stages of potato. The upper soil layer (0-30 cm) contributed relatively more moisture with frequent supply of water (irrigation at 1.6 IW/CPE ratio receiving 5 irrigations in all). Crop in other irrigation treatments having 3-4 irrigations extracted relatively more moisture from deeper (60-120 cm) soil profile. Potato + french bean system recorded similar PEY and WUE (based on PEY) to that of sole potato, but had LER values greater than 1 in both the seasons.